A Few Preliminary Reflections on Religious Studies and Covid-19 - Yuli Andriansyah (Millah: Journal of Religious Studies, 2021)
The pandemic of COVID-19 has had a significant impact on religious studies. Numerous religious studies courses have transitioned to online learning, necessitating instructors to modify their instructional strategies and materials. Virtual worship services have become prevalent, allowing religious communities to adhere to social distancing guidelines while continuing to practice their religion. Religious studies scholars have examined the impact of the pandemic on religious beliefs and practices, including the significance of interfaith cooperation and the crisis's ethical implications. The pandemic has presented scholars, instructors, and practitioners in religious studies with both challenges and opportunities to adapt and respond to changing circumstances.